Pelatihan English for Tourism Berbasis Communicative Language Teaching untuk Staf Dinas Pariwisata dan Kebudayaan Kabupaten Kudus - Fitri Budi Suryani; Rismiyanto Rismiyanto; Sri Endang Kusmaryati (Universitas Muria Kudus, 2021)
Kudus is one of the regencies in Indonesia that has a lot of tourism potential such as nature, pilgrimage, and culinary tourism. The number of domestic and foreign tourists visiting Kudus increases every year. However, this enormous tourism potential is not adequately supported by the tourism human resources. Many staffs of tourism and culture department of Kudus still lack of English for tourism proficiency to interact with foreign tourists. This community service aims at increasing the English for tourism proficiency of the staffs of the tourism and culture department of Kudus through Communicative Language Teaching (CLT) based English training. This training was completed with role play practice in Cigarette museum of Kudus. Through this training, the staffs of tourism and culture department of Kudus can have good English for tourism proficiency that make them able to interact with foreign tourists and in the end increase tourism in Kudus. Kata kunci: English for tourism, pariwisata, communicative language teaching, staf dinas pariwisata dan kebudayaan